The Misappropriation of Public Infrastructure, Facilities, and Utilities (PSU) Land for Private Residential Ownership: An Indonesian Land Law Analysis of Sigura Gura Residence Housing Estate in Malang City - Shang Dyah Pitaloka; Herlindah Herlindah; Supriyadi Supriyadi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the factors underlying the transfer of infrastructure, facilities, and public utilities (PSU) land into residential ownership and to examine its juridical and social consequences for residents of Sigura Gura Residence Housing in Malang City. This research employs an empirical legal method with a juridical-sociological approach through statutory, conceptual, and case approaches. The findings reveal that the transfer of PSU land was caused by weak governmental supervision, inadequate land administration, developers’ economic orientation, and delays in the handover of PSU. The conversion of a mushola into residential property resulted in juridical consequences in the form of violations of the social function of land principle and inconsistencies with the approved housing site plan. Socially, the practice led to the loss of worship facilities and communal interaction spaces, thereby affecting residents’ rights to a proper and sustainable living environment.